Analysis of the anti-apoptotic v-Bcl2 and v-Flip genes and effect on in vitro programmed cell death of Argentinean isolates of bovine gammaherpesvirus 4 (BoHV-4). (July 2020) - Morán, Pedro; Manrique, Julieta; Pérez, Sandra; Romeo, Florencia; Odeón, Anselmo; Jones, Leandro; Verna, Andrea
Abstract: Some viruses encode inhibitory factors of apoptosis during infection to prolong cell viability and then to achieve a higher production of viral progeny or facilitate persistent infections. There is evidence that some gammaherpesviruses, including BoHV-4, carry genes that can both inhibit or induce apoptosis. BoHV-4 possesses two genes (ORF16 and ORF71) that code for proteins with anti-apoptotic functions, such as v-Bcl2 and v-Flip, respectively. Thus, it is relevant to study BoHV-4 in relation to the modulation of apoptosis in infected cells as a strategy for persistence in the host. The objective of this work was to analyze whether variations in v-Flip and v- Bcl2 of six phylogenetically divergent Argentinean isolates of BoHV-4 can influence the capacity of these strains to induce apoptosis in cell cultures. In this study, variations were mainly detected in the v-Flip gene and protein of the BoHV-4 strains belonging to genotype 3. Thus, it is possible to infer that sequence variations could be associated with some BoHV-4 genotype. Induction of apoptosis was not a significant event for any of the genetically distinct local isolates of BoHV-4 and there was not an evident relationship between the variability of both genes with the apoptotic effect of the phylogenetically distinct strains. Highlights: v-Flip and v-Bcl2 were amplified in four out of six BoHV-4 strains. Variations detected in both genes resulted in changes in the respective proteins. Most of the variations were detected in genotype 3 strains. The variations were particularly evident in v-Flip gene and protein. The genetic variations of these genes could be associated with the viral genotype.